Tantangan Keluarga Broken Home (Studi Tentang Motivasi Belajar Siswa Di Smp Negeri 2 Ngantru Tulungagung) - Denis Nuranisa Ikhsani; Anggoro Putranto (Departement of Mathematics Education, 2024)
This research aims to determine the influence and impact of a broken home family on student learning motivation at SMP Negeri 2 Ngantru Tulungagung. Using quantitative methods and data analysis using SPSS. The results of the research show that there is a significant influence between broken home families on student learning motivation. The results of the correlation test using Product Moment show a significance value of 0.008<0.05, indicating that the two variables are significant. Simple Linear Regression results also support this finding with a significance value of 0.008, which is in accordance with the guidelines that a significance value <0.05 indicates a significant effect. Therefore, it can be concluded that the Ha hypothesis is accepted and H0 is rejected, which means that broken home families have a significant and negative effect on student learning motivation at SMP Negeri 2 Tulungagung.